Cost‐effectiveness of an in‐home respite care program to support informal caregivers of persons with dementia: A model‐based analysis. (13th February 2020) - Vandepitte, Sophie; Putman, Koen; Van Den Noortgate, Nele; Verhaeghe, Nick; Annemans, Lieven
Abstract: Objectives: To evaluate cost‐effectiveness of an in‐home respite care program in addition to standard community‐based dementia care to support informal caregivers of persons with dementia compared with standard community‐based dementia care. Methods: An age‐dependent decision‐analytic Markov model was applied from a third‐party payer and a societal perspective projecting results of a quasi‐experimental study over a time horizon of 5 years assuming a repetition of the program every 6 months. Additionally, to deal with uncertainty and to test robustness of the model scenario, one‐way and probabilistic sensitivity analyses were conducted. Results: Implementing the program resulted in a quality‐adjusted life year (QALY) gain of 0.14 in favor of the invention group compared with controls and an incremental cost of 1270€ from the third‐party payer perspective and of 1220€ from the societal perspective. Next, an incremental cost‐effectiveness ratio of 9042€/QALY and of 8690€/QALY was found in the base case, from the third‐party payer perspective and the societal perspective, respectively. The scenario, one‐way sensitivity, and probabilistic analyses demonstrated robustness of the base‐case results. Conclusion: This cost‐effectiveness analysis suggests that an in‐home respite care program in addition to standard community‐based dementia care is a cost‐effective approach compared with standard community‐based dementia care only. These findings provide more insight into the value of such services for the patient, the caregiver, and for society.